Multiwavelength source based on SOA and EDFA in a ring-cavity resonator - Shahi, Sharifeh; Harun, Sulaiman Wadi; Sulaiman, Abdul Hadi; Thambiratnam, Kavintheran; Ahmad, Harith (John Wiley & Sons, 2009)
A multiwavelength source incorporating a semiconductor optical amplifier (SOA) and a erbium-doped fiber amplifier (EDFA) in a ring-cavity configuration was demonstrated. The multiwavelength source was able to generate more than 13 channels at -27 dBm and above at a SOA bias current of 300 mA and 980-nm pump power of 92 mW. The number of wavelengths generated can be controlled by adjusting the birefringence of the ring cavity using the polarization controllers. The proposed laser has constant channel spacing of 0.8 nm, which is suitable for communication and sensing applications, and shows stable operation at room temperature.